AB0301 Characteristics of rheumatoid arthritis patients with adverse effects after the initiation of tocilizumab therapy. (23rd January 2014) - Diaz-Torne, C.; Ortiz, M. A.; Hernandez, M. V.; Reina, D.; Castellví, I.; De la Fuente, D.; Magallares, B.; Ruiz-Martin, J. M.; Corominas, H.; Geli, C.; Sanmartí, R.; Llobet, J. M.; et al.
Abstract : Background: Tocilizumab is a humanized monoclonal antibody that blocks IL-6 mediated pro-inflammatory signalling in rheumatoid arthritis patients. The safety profile of tocilizumab has been extensively evaluated in clinical trials. However, there is little data on markers at the initiation of tocilizumab therapy that may predict the development of adverse effects requiring drug withdrawal. Objectives: To identify markers that predict the development of secondary effects that required drug withdrawal the 6 first months after initiating tocilizumab therapy. Methods: Forty-six rheumatoid arthritis patients treated with tocilizumab in routine clinical practice were retrospectively evaluated 24 weeks after initiating therapy. Demographic and clinical data, complete blood cell counts, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), titers of rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibodies, serum cytokines (IL-6, IL-15 and IL-17) and the frequency of activated CD4+, CD8+ and Treg cells were collected before tocilizumab administration (baseline). Characteristics of patients with and without adverse effects were compared. Results: Twelve (26.1%) patients developed adverse effects that required drug withdrawal during the first six months of tocilizumab therapy. Seven patients suffered an allergic or infusional reaction and two patients had neutropenia. All recovered after drug withdrawal. Two further patients suffered an infection requiring hospitalization (salpingitis and periappendiceal abscess) and one patient had a myocardial infarction. Patients with and without adverse effects had comparable ages and disease evolution. Patients with adverse effects had lower neutrophil counts (4.1±2.6 vs 5.6±1.8, p<0.05) and lower DAS28-CRP (5.1±1.2 vs 4.3±1.2, p<0.05) at baseline than those without. No significant differences in IgG, IgM and IgA were observed between the two groups. However, fewer patients with higher CRP, titers of anti-CCP antibodies, or serum concentrations of IL-6 and IL-15 were observed in the group with adverse effects (Table 1 ). There were no differences in the frequency of T cell subsets and Tregs between patients with and without adverse effects before the treatment. Conclusions: Patients with adverse effects presented fewer prognostic markers of severe disease. Higher levels of some markers (CRP, anti-CCP antibodies, IL-6, IL-15 and neutrophil counts) may identify patients less likely to suffer adverse effects due to tocilizumab therapy. Disclosure of Interest: None Declared